2020
DOI: 10.1111/add.15003
|View full text |Cite
|
Sign up to set email alerts
|

Cannabis use and stressful life events during the perinatal period: cross‐sectional results from Pregnancy Risk Assessment Monitoring System (PRAMS) data, 2016

Abstract: Aims We aimed to determine the association between stressful life events (SLEs) in the year prior to childbirth with (1) pre‐pregnancy cannabis use, (2) cessation of cannabis use during pregnancy and (3) postpartum relapse to cannabis use. Design We used data from the Pregnancy Risk Assessment Monitoring System (PRAMS) 2016, a cross‐sectional, population‐based surveillance system. Setting Mailed and telephone surveys conducted in five states—Alaska, Colorado, Maine, Michigan and Washington—in the United States… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 23 publications
3
16
0
Order By: Relevance
“…Several studies that investigate the role of major life events (e.g., natural disasters, 11 community violence, 12 trauma or abuse 13 ) and stress, 14 have identified that individuals are likely to increase their substance use (including use of cannabis), in the period immediately following the disaster or traumatic event. [15][16][17][18] When analyzing cannabis use and stressful life events in pregnant women, Allen et al (2020) found that women who experienced stressful life events the year prior to giving birth were more likely to use cannabis during the perinatal period. 19 The purpose of the COVID-19 Cannabis Health Study is to provide data from an electronic self-report questionnaire to assess patterns and trends of possible SARS-CoV-2 exposure, behaviors that may be related to its transmission, and the prevalence of COVID-19 given testing among a group of adult MCUs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies that investigate the role of major life events (e.g., natural disasters, 11 community violence, 12 trauma or abuse 13 ) and stress, 14 have identified that individuals are likely to increase their substance use (including use of cannabis), in the period immediately following the disaster or traumatic event. [15][16][17][18] When analyzing cannabis use and stressful life events in pregnant women, Allen et al (2020) found that women who experienced stressful life events the year prior to giving birth were more likely to use cannabis during the perinatal period. 19 The purpose of the COVID-19 Cannabis Health Study is to provide data from an electronic self-report questionnaire to assess patterns and trends of possible SARS-CoV-2 exposure, behaviors that may be related to its transmission, and the prevalence of COVID-19 given testing among a group of adult MCUs.…”
Section: Introductionmentioning
confidence: 99%
“…[15][16][17][18] When analyzing cannabis use and stressful life events in pregnant women, Allen et al (2020) found that women who experienced stressful life events the year prior to giving birth were more likely to use cannabis during the perinatal period. 19 The purpose of the COVID-19 Cannabis Health Study is to provide data from an electronic self-report questionnaire to assess patterns and trends of possible SARS-CoV-2 exposure, behaviors that may be related to its transmission, and the prevalence of COVID-19 given testing among a group of adult MCUs. The objectives of this study were (1) to provide data on selfreported behavioral changes among adult MCUs since COVID-19 was declared a pandemic, characterized by preexisting chronic health conditions; and (2) to provide prevalence estimates of COVID-19 symptoms, testing, and infections among adult MCUs.…”
Section: Introductionmentioning
confidence: 99%
“…Research by Allen et al [1]-published in this issue-provides several important contributions, but none stands out more clearly than the finding that approximately one in three women reporting cannabis use prior to becoming pregnant continue to use cannabis during pregnancy. This is a disconcerting discovery, particularly in light of evidence that prenatal cannabis exposure is related to key neonatal [2] and, potentially, longer-term deleterious developmental outcomes [3].…”
mentioning
confidence: 99%
“…
As we consider the evidence related to continued cannabis use during pregnancy—and develop programs to target this issue—it is vital we consider how distal and proximal stressors, including those related to social disadvantage, influence perinatal cannabis use risk over time .
Research by Allen et al . [1]—published in this issue—provides several important contributions, but none stands out more clearly than the finding that approximately one in three women reporting cannabis use prior to becoming pregnant continue to use cannabis during pregnancy. This is a disconcerting discovery, particularly in light of evidence that prenatal cannabis exposure is related to key neonatal [2] and, potentially, longer‐term deleterious developmental outcomes [3].…”
mentioning
confidence: 99%
See 1 more Smart Citation